Strengthening Women’s Economic Independence through Creative Economy-Based Community Empowerment by Optimizing Local Banana Resources in Tongkaina Village - Kayla A Ch Sudarto; Precylia Ribka Rambing; Edryl Ponggohong (LPPM Institut Pendidikan Nusantara Global, 2026)
Women’s empowerment based on the creative economy is a strategic approach to strengthening community economic independence, particularly in rural areas. This research was conducted in Tongkaina Village, which possesses abundant banana resources that have not been optimally utilized. The empowerment program was designed to enhance women’s economic capacity through the application of appropriate technology and market diversification strategies. The program focused on processing banana plants into value-added products such as banana leaf tea, banana chips, and banana fiber-based handicrafts. Using a mentoring and participatory approach, the program involved 25 women participants who received training in production techniques, basic business management, and marketing strategies. The results indicate that approximately 50% of participants experienced improved production skills, while average household income increased by around 80% after the implementation of the program. In addition to economic benefits, the program strengthened women’s self-confidence, entrepreneurial motivation, and active participation in community economic activities. Furthermore, social impacts were observed in the form of increased solidarity, cooperation, and collective awareness among women in utilizing local resources sustainably. Overall, this study demonstrates that creative economy-based empowerment using local banana resources can serve as a replicable and sustainable empowerment model for other rural villages with similar natural resource potential.